WTO accession and growth: Tang and Wei Redux - André Brotto; Adam Jakubik; Roberta Piermartini (World Trade Organization (WTO), 2021)
On the occasion of the 25th anniversary of the WTO, this paper re-estimates the impact of WTO accession on growth. Joining the multilateral trading system not only expands access to international markets but also requires commitment to domestic reforms. Tang and Wei (2009) showed that there is in fact a positive effect of WTO on growth also during the period of accession when these commitments are undertaken. In this paper, we extend Tang and Wei's analysis to the sample of 32 newly acceded countries. We find that WTO accession is associated with a significant positive increase in GDP growth. This effect is larger than previously estimated. We find that five years after accession an economy is 30% larger, and that the impact of WTO entry on growth persists beyond the first five years.
Keywords: F1; 330; Dynamic gains from trade; economic growth; trade liberalization; newly acceded countries; Article XII countries